Pre-treatment of used cooking oil followed by transesterification reaction in the production of used cooking oil-based polyol / Radin Siti Fazlina Nazrah Hirzin and Siti Nurzubaida Shahdan - Nazrah Hirzin, Radin Siti Fazlina; Shahdan, Siti Nurzubaida (Universiti Teknologi MARA, 2021)
Used cooking oil has been considered as an economical and sustainable material that can be used widely as a starting material in the production of polymer precursors such as polyol for polyurethane. Since the composition of fatty acids and glyceride in the structure of used cooking oil remain the same as virgin vegetable oil, used cooking oil can be synthesized using the same method. However, there are certain physicochemical modifications to the oil properties that arise during the process of oil frying's such as increases in viscosity, acid value, and color changes that will affect the conversion of used cooking oil into bio-based polyol. Thus, various pretreatment methods that can be applied to used cooking oil such as adsorption, chemical bleaching, and treatment with solvents will be reviewed in this paper. Transesterification of used cooking oil with alcohol in the presence of catalyst will produce used cooking oil-based polyol which will have two or more hydroxyl groups per molecule. The formation of polyol can be confirmed with the formation of O-H peak in the FTIR spectrum during the FTIR spectroscopy analysis. This paper will also discuss the type of alcohol and catalyst used in the transesterification reaction. Used cooking oil-based polyol obtained from transesterification reaction has been reported to be comparable to the commercial polyol.